Analisis dan Pengukuran Tanggapan Frekuensi terhadap Redaman Serat Optik - Uzma Septima -; Lince Markis -; Ramiati - -; Andi Ahmad Dahlan; Sri Nita - (Jurnal Ilmiah Poli Rekayasa, 2020)
The concept of smart home and cyber home is not the same, even much different. If a smart home or smart home is more aimed at users or home users who lead to conventional homes equipped with digital devices, the concept of cyber home is more to the bandwidth capacity of the internet to complement digital devices in the home. For this reason, Cyber Park Indonesia cooperates with PT Wika Realty. Specifically to develop the housing as a cyber home, Cyber Park Indonesia uses optical fiber. [Kompas, 2017]. This fact states that communication using optical fiber becomes very important so that to optimize the optical fiber system, a study that produces frequency responses to optical fiber attenuation parameters is made. Various sine signal frequency and amplitude values are given as input from an optical fiber dispersing system by looking at the response of the receiver in the form of voltage parameter values. The frequency values given range from 100 Hz to 10 Khz. The linkage of the input amplitude value to the damping value is an output voltage output generated by the amplitude of the amplitude parameter at the sending end. This voltage value comparison is used as the damping parameter of an optical fiber communication system. Giving this frequency will provide the performance of a fiber optic communication system. The resulting voltage value is a constant of changes in the frequency value.